Pentingnya Literasi Keuangan Remaja bagi Siswa SMKN 1 Kota Tangerang - Metta Susanti; Rina Sulistiyowati; David Kiki Baringin MT Samosir; Henry Gunawan; Yanti Puspa Rini (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Recently, the public has been shocked by the high number of bad debts among Millennials. The development of digital technology brings various conveniences, but also presents new threats to children and teenagers. The high percentage of online loan borrowers aged 19-34 years, as well as children who are caught in online gambling, is a major concern. Around 60 percent of online loan users (pinjol) have an easy target of young people aged 19-34 years, and even 80 thousand children under the age of 10 are caught in online gambling (judol). The problem is, the Millennial generation or those aged 19-34 years are the largest "contributors" to these bad debts. Various experts say that the Millennial generation is in debt because of the Fear of Missing Out (FOMO) phenomenon, aka following trends so as not to feel "left behind". Some other experts think that their financial literacy is low.